Attention–deficit/hyperactivity disorder symptoms, perceived stress, and suicidal ideation during the COVID-19 pandemic - Stickley, Andrew; Shirama, Aya; Inagawa, Takuma; Ruchkin, Vladislav; Koposov, Roman; Isaksson, Johan; Inoue, Yosuke; Sumiyoshi, Tomiki (Frontiers in Psychiatry, 2022)
Objective: Attention-deficit/hyperactivity disorder (ADHD) symptoms have been linked to suicidal behavior. However, little is known about the mechanisms involved in this association. This study examined ADHD symptoms and suicidal ideation during the COVID-19 pandemic and the role of self-perceived stress in this association. Method: Data were analyzed from an online sample of 1452 Japanese individuals aged 18 to 89 obtained in February 2021. Information was collected on past-year suicidal ideation. ADHD symptoms were assessed with the Adult ADHD Self-Report Scale (ASRS) Screener while stress was measured with the Perceived Stress Scale (PSS-14). Depressive symptoms were assessed with the Patient Health Questionnaire (PHQ-9), while the Generalized Anxiety Disorder scale (GAD-7) was used to assess anxiety symptoms. Logistic regression was used to examine associations. Results: Fifty-one (3.5%) individuals had ADHD symptoms, while more than one in ten (11.7%) of the respondents reported past-year suicidal ideation. In an analysis adjusted for sociodemographic factors, ADHD symptoms were associated with eight times higher odds for past-year suicidal ideation. However, adjusting the analysis for mental health variables (anxiety and depressive symptoms) attenuated the association which became non-significant (odds ratio [OR]: 1.96, 95% confidence interval [CI]: 0.92-4.18). In contrast, in an analysis adjusted for mental health, individuals with ADHD symptoms and stress had significantly higher odds for suicidal ideation (OR: 3.72, 95%CI: 1.43-9.67) whereas ADHD symptoms without stress were not linked to suicidal ideation (OR: 1.25, 95%CI: 0.38-4.18). Conclusions: Self-perceived stress may play a role in is important in the association between ADHD symptoms and suicidal ideation among individuals in Japan during the COVID-19 pandemic. Detecting and managing stress and its effects in individuals with ADHD/ADHD symptoms should be a therapeutic focus for improving health-related outcomes in this population both during the COVID-19 pandemic and beyond.